Peningkatan Hasil Belajar IPA Materi Siklus Air Menggunakan Kombinasi Model Problem Based Learning, Mind Mapping Dan Media Gambar Kelas V SDN Aluh-Aluh Besar 2 Kabupaten Banjar - Herlina; Susilawaty (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
The problem of this research is that learning still uses the lecture method and the low learning outcomes of science content on water cycle material in class V SDN Aluh-Aluh Besar 2 Kabupaten Banjar regency which results in passive students, lack of cooperation with friends and low student learning outcomes. The solution to overcome these problems is to do learning with the problem based learning, mind mapping and picture media. This study aims to describe teacher activities, analyze student activities and student learning outcomes in the water cycle material. This study used a qualitative approach with the type of CAR Classroom Action Research, which was carried out in three meetings. The research subjects were fifth grade students in the even semester of SDN Aluh-Aluh Besar 2 Kabupaten Banjar in the academic year 2022-2023, with a total of 9 students. The data were analyzed qualitatively through research instruments in the form of observation sheets of teacher and student activities as well as learning achievement tests which were described in the form of observation sheets of teacher and student activities as well as learning achievement tests which were described in the form of tables and graphs. Then they were interpreted using the criteria for each indicator of the success of teacher and student activities, as well as the achievement of individual student learning completeness and classic.